Incidence of Retinopathy in Newly Diagnosed Patients with Type-II Diabetes Mellitus - Shahid Anwar Bhatti, Hafiz Muhammad Ahmad, Muhammad Ayub Khan, Zaheer Uddin Babar, Abdul Rafe, Waleed Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the incidence of retinopathy in patients newly diagnosed with type-II diabetes mellitus. Place and Duration: Alshifa Trust Eye Hospital, Rawalpindi and Ophthalmology Department, CMH, Lahore for six-months duration from January 2022 to June 2022. Methods: The study included 200 individuals with type 2 diabetes mellitus diagnosed within the previous two months and selected with non-probability consecutive sampling technique. Diabetes was diagnosed on the basis of two consecutive values of random blood glucose (RBS), fasting blood glucose (FBS) and glycosylated hemoglobin (HBA1c)> 200 mg / dL according to the following criteria defined by the World Organization (WHO) which was revised in 1999 and 2006. All patients underwent detailed examination of the retina for diabetic retinopathy evaluation using biomicroscopic slit lamp and +90 Diopter lens. SPSS-21.0 was used for the data analysis. For each variable, descriptive statistics were calculated. Results: 200 patients in total were enrolled in this study. The participants ranged in age from 31 to 60 years, with the majority were in the 4th decade (mean age: 51.50 ± 9.02). 30 individuals (15%) with newly diagnosed type 2 diabetes had diabetic retinopathy. From 30 patients of newly diagnosed type 2 diabetes mellitus; the background retinopathy was seen in 18 (60%) of patients, pre proliferative retinopathy was observed in 8 (26.7%) of patients and proliferative retinopathy was seen in 3 (13.3%). Patients with diabetic retinopathy had a HbA1C (%) of 9.8± 1.2, while those without the diabetic retinopathy had HbA1c of 7.1 ± 2.2. Conclusions: We found that the incidence of retinopathy in patients with newly diagnosed type 2 diabetes is 15%, which underlines the value of a comprehensive ophthalmological assessment of all diabetic patients at diagnosis. Keywords: Retinopathy, Type-II diabetes mellitus and incidence.